Модернизация как способ распространения глобальных рисков (Արդիականացման գործընթացը գլոբալ ռիսկերի տարածման միջոց) - Դունամալյան Նորայր (YSU Journal of International Affairs, 2016)
The article analyzes the contemporary processes of modernization and globalization as a way to spread global risk due to mismatch of modernist and traditional values. "Technological" model of modern social and political relations considers culture as an instrument for achieving certain political objectives. The logic of the development of modern non-Western societies is also based on the values of good governance and, as a rule, formulated on the basis of the simulation elements of the political project of Modernity. There is also a modern technocratic society, the problem of man and the need to create conditions for rethinking the role and man’s place in the global world of the future.